Country in the city : agricultural functions of protohistoric urban settlements (Aegean and Western Mediterranean) - Garcia, Dominique; Garcia, Dominique; Zurbach, Julien; Zurbach, Julien; Pomadère, Maia; Pomadère, Maia; Orgeolet, Raphaël; Orgeolet, Raphaël (Archaeopress archaeology, 2019)
Assembles contributions on the place of agricultural and Early Iron Age Mediterranean, concentrating on the second-millennium Aegean and the protohistoric north-western Mediterranean